Information Technology Governance Audit at XYZ College Using COBIT Framework 2019 - Samsinar, Samsinar; Sinaga, Rudolf (BERKALA SAINSTEK, 2022)
Reliable and up-to-date information services are one of the parameters for the achievement of an organization's performance, including for a university, which is currently required to be able to adapt to technological advances to produce graduates who can master information technology to support the competence of their respective fields. The curriculum changes launched by the current government are also proof that the application of information technology in higher education is a must. Seeing this, universities have a difficult task, especially at the implementation stage of implementing information technology, because they must prepare not only infrastructure but also human resources who can develop good information system governance. Therefore it is necessary to carry out an IT governance audit. From the results of observations made, XYZ College has utilized information technology in academic services and other information services. However, it was found that information technology governance does not yet have a standard so that it is considered not to be able to meet the desired goals, and instead will cause various problems including uncontrolled operational costs and other problems. The purpose of this study is to measure the performance of information technology governance at XYZ College using the COBIT 2019 framework. Based on the results of an audit conducted from 7 EGIT components, namely processes, organizational structure, information flow and items, people skills and competencies, policies and procedures, culture, ethical behavior, and service infrastructure and application are on average at level 3, it can be concluded that the application of information technology has been running, the infrastructure is adequate but does not have good governance procedures or standards. It is recommended that XYZ Higher Education make standards for information technology governance as well as periodic evaluations of the use of all components of information technology, both software, hardware, and brainware.